2019
DOI: 10.1177/1055665619851650
|View full text |Cite
|
Sign up to set email alerts
|

“Exposed and Vulnerable”: Parent Reports of Their Child’s Experience of Multidisciplinary Craniofacial Consultations

Abstract: Objective: Childhood is a period of extensive socioemotional development, which can be impacted by the presence of a congenital craniofacial anomaly (CFA). Complex multidisciplinary treatment and long-term follow-up are normally required, yet understanding of children’s treatment experiences is limited. The objective of this study was to investigate children’s experiences of multidisciplinary team (MDT) consultations from the perspective of their parents. Design: Thirty-eight parents of children with a rare CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…M. Nelson, 2002). Nonetheless, parents remained reluctant to bring the issue forward, even when some children had asked questions about their appearance, fearing they would generate insecurities or engender appearance concerns, as also demonstrated in a recent study on parents of children with a visible difference (Feragen et al, 2019), and in other medical conditions (Middleton et al, 2018;O'Toole et al, 2021). Self-doubt has been described as prevalent in mothers of children with disabilities (A. M. Nelson, 2002), an understandable and normal reaction to unusual circumstances.…”
Section: Talking About Appearance: a "Double-edged Sword"mentioning
confidence: 99%
See 1 more Smart Citation
“…M. Nelson, 2002). Nonetheless, parents remained reluctant to bring the issue forward, even when some children had asked questions about their appearance, fearing they would generate insecurities or engender appearance concerns, as also demonstrated in a recent study on parents of children with a visible difference (Feragen et al, 2019), and in other medical conditions (Middleton et al, 2018;O'Toole et al, 2021). Self-doubt has been described as prevalent in mothers of children with disabilities (A. M. Nelson, 2002), an understandable and normal reaction to unusual circumstances.…”
Section: Talking About Appearance: a "Double-edged Sword"mentioning
confidence: 99%
“…For parents, feelings of shock, grief, anger, guilt, and/ or anxiety about the child's future are common following their child's diagnosis (Klein et al, 2006; A. M. Nelson, 2002;Pope et al, 2005). Parents must support their children through a series of surgical interventions (Feragen et al, 2019), many of which will change their child's appearance. Although previous research has found parents to be satisfied with the outcomes of their children's appearance following surgery (Feragen & Stock, 2017), parents must nonetheless face what is experienced as the challenging task of making difficult decisions on their child's behalf (van Manen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research with parents of children with burn injuries or craniofacial conditions has illustrated that the desire to protect their children can result in the restriction of social activities outside of the home and educational opportunities that parents perceive as threatening. 12,52 Siblings of burn-injured children have also reported less involvement in school activities and lower social competence when compared to a normative sample. 53 Therefore, it is important to consider the potential impact of a parent's increased desire to protect their children, in terms of their child's social and emotional development.…”
Section: Discussionmentioning
confidence: 99%
“…The standard team structure, consultation processes, and use of telemedicine differ across sites and countries. For example, in Malaysia and certain countries, depending on the healthcare institution, an average of 5-15 health professionals may attend multidisciplinary combined clinics [28,29]. The number of patients typically seen on a consultation day varies from week to week.…”
Section: Multidisciplinary Cleft Carementioning
confidence: 99%